Women Farmers In The Forest Area - Sukesi, Keppi (Opción, 2019)
This study aims to analyse the socio-economic and gender aspects of water and soil resource management, biodiversity, and climate change in the Bangsri watershed. Specifically, efforts to (1) present the results of the research on the socio-economic and gender aspects in 5 research areas in the Bangsri Water- shed, Malang, East Java; (2) analyse the socio-economic conditions and gender profiles and (3) to formulate draft recommendations for project interventions to improve the socio-economic and gender conditions in the 5 Micro-DAS re- search areas. This research used Focus Group Discussions, Rapid Rural Ap- praisal (RRA), in-depth interviews, and secondary data studies at the village level. This survey was conducted in 5 Micro-DAS research areas, namely Bangsri Watershed, Wajak District, Malang Regency in four selected villages; Bambang, Dadapan, Patokpicis, and Bringin and one village in Turen, Sanan- kerto village, involving 120 respondents in total. The results show that 1) the community is aware of the limitations of biodiversity and climate change, 2) the community uses local wisdom to plant crops and 3) decision-making in the village is still gender biased, as males in society take on the role of production while women get traditional roles.